The Impact of Psychological Resources on Body Mass Index in Obesity Surgery Candidates - Robitzsch, Anita; Schweda, Adam; Hetkamp, Madeleine; Niedergethmann, Marco; Dörrie, Nora; Herpertz, Stephan; Hasenberg, Till; Tagay, Sefik; Teufel, Martin; Skoda, Eva-Maria (Frontiers in Psychiatry, 2020)
Background: Obesity surgery is the therapy of choice for severely obese patients. The results are promising, but at the same time obesity surgery represents a physical and psychological challenge for patients and care givers. In order to give psychosocial support adequately, more knowledge of effects of psychological profiles is required. Research is often deficit and symptom oriented. Psychological resources (competences) of individuals are often neglected. However, after surgery patients have to cope with the altered anatomic condition and therefore psychological resources are essential for a successful development and my influence also the surgical outcome. The interplay of eating behavior, depression, and psychological resources and their influence on weight are yet undetermined. Methods: A cross-sectional study in consecutive obesity surgery candidates was performed. 127 participants were included (90 female, 37 male; mean BMI 49.85 kg/m²; range 36.7 kg/m² to 84.2 kg/m²). After conducting semi-structured clinical interviews psychological resources (ERI), depression (PHQ-d) and eating behavior were assessed (EDE-Q). To evaluate the influence of psychological resources on BMI mediation models and path analyses were performed. Results: Psychological resources don’t influence BMI directly. Path analyses revealed depression as well as depression/eating behavior as mediating dimension. The first path showed that higher psychological resources lead to less depressive symptoms and lower BMI. The second path showed that higher psychological resources lead to less depression and by means of more conscious and controlled eating behavior to a lower BMI Conclusion: Psychological resources seem to be relevant in the context of obesity surgery. Good psychological resources lead to less depression and a more adequate eating behavior. The evaluation of psychological resources in obesity surgery candidates allows the identification of patients at risk. Competences of patients should be addressed in the context of surgery. Our findings build a foundation for a more individualized supportive treatment for obesity surgery candidates. Improving impaired psychological resources may help in the coping process after surgery and is supposed to lead to an even higher weight loss.